(untitled) (Health Renaissance, 2011)
Introduction: Health camp is a strategy of mental health service delivery. The present study was conducted to find out psychiatric morbidity pattern seen in camp in a village of eastern Nepal. Method: Information about all relevent variables of the cases seen by a psychiatrist team in a specialty camp were recorded in a particular record-book. We used the ICD-10 for the diagnosis of mental and behavioral disorders. The data recorded were analysed using descriptive statistical measures. Result: Of 160 cases analysed, 106 (66.25%) were female. The most common age groups were 35-39 (20%), 20-24 (11.25%) and 40-44 (11.25%). The most common psychiatric diagnoses in the Nepalese camp setting were depressive, somatoform and anxiety disorders. Primary headaches and seizure disorders were also common. Four cases (2.5%) were acutely severe and were in the immediate need of intervention. Conclusion: Most common psychiatric diagnoses were mood, somatoform and anxiety disorders in Nepalese camp setting. Some require urgent attention and admission. This indicates a need for regular mental health camp programs in our set up. Keywords: Health camp; mental health service; Nepal; Psychiatric morbidity DOI: 10.3126/hren.v8i3.4213 Health Renaissance, September-December 2010; Vol 8 (No.3);186-191